Research progress of E3 ubiquitin ligase regulating biological behavior of human placental trophoblast cells - Feng, Jun; Yin, Huimei; Baturuhu,; Dai, Yonghui; Dai, Fuxiao; Xu, Junjun; Chen, Zhili; Liu, Yanyan (Frontiers in Endocrinology, 2023)
E3 ubiquitin ligases are important components of the ubiquitin protease system. This family includes many proteins, which can catalyze the ubiquitination of a variety of protein substrates and promote their degradation by the proteasome system. Recent studies have shown that E3 ubiquitin ligase plays a key role in the process of fetal development and placental formation. It affects the biological behavior of placental trophoblast cells, leading to a series of pregnancy complications that threaten mothers and babies greatly. This review focuses on the regulation, target and mechanism of E3 ubiquitin ligase on the biological behavior of human placental trophoblast cells.